An Analysis of Mercury (Hg) Levels in Face Whitening Cream Product - Getrina Septia Azita; Dian Mayasari (Jurnal Ilmu Kesehatan Abdurrab, 2023)
ABSTRACT Facial whitening cream is a mixture of chemicals and other ingredients with the aim of whitening the skin or lightening black spots on the skin. Mercury is used as an active substance that is added to facial whitening creams that have the ability to inhibit melanin, so you get brighter skin in a short time. Long-term use will cause the skin to turn blue-black and can trigger cancer. This study aims to determine the presence or absence of mercury (Hg) compounds and the levels in face whitening creams with brands A, B, C, D. Tests were carried out using qualitative and quantitative analysis, this sampling technique was carried out randomly. Qualitative analysis was carried out using 0.5 N KI reagent while quantitative analysis was carried out using Atomic Absorption Spectrophotometry to determine levels of mercury compounds (Hg). The results of the qualitative analysis showed that 1 sample contained positive mercury (Hg) which was indicated by the formation of an orange precipitate with a concentration of â‰¤ 0.1 Âµg/kg.